Enterprise Digitalization Enabling Supply Chain Development: Driving Mechanisms and Path Choices - Cui, Kailing; Zhang, Xuxin; Zou, Jing; Huang, Yi; Rui, Xiqian (Transactions on Economics, Business and Management Research, 2023)
With the emergence and popularization of emerging digital technologies such as big data and artificial intelligence, it provides a new direction of thinking for enterprises to optimize supply chain layout and empower supply chain development. Promoting the synergistic and efficient development of the supply chain is a key issue that enterprises need to explore urgently. This paper takes the enterprise supply chain development as the research object, takes the enterprise digital transformation as the starting point, and deeply analyzes the mechanism and path of enterprise digital empowerment supply chain development. This paper explores the influence path of enterprise digitalization on supply chain development from the aspects of enterprise innovation ability and financing constraints, and puts forward suggestions and countermeasures for the dilemmas faced by enterprises in digital transformation, and the results of the research have certain practical significance for supply chain management.